2009
DOI: 10.1007/s00105-009-1828-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeted UVB-308 nm (NUVB) therapy with excimer laser in the treatment of atopic dermatitis and other inflammatory dermatoses

Abstract: UVB 311 nm phototherapy (NUVB) is used successfully in the treatment of psoriasis or atopic dermatitis and is often chosen as "first-line" therapy. In a prospective study we investigated the efficacy of the targeted UVB 308 phototherapy by excimer laser in the treatment of 57 patients with localized, mild therapy-resistant atopic dermatitis. We achieved a complete remission (CR) in nearly 85% and a partial remission (PR) in 15% after 10 treatments during 6-8 weeks in all patients. A mean reduction in patient-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Other devices such as 308-nm monochromatic excimer laser expand the therapeutic options in patients with localized and therapyresistant AE even though they can treat only limited surfaces. 182,183 Pulsed-dye laser for the treatment of chronic AE is still experimental. 184 Currently, the mainstay for phototherapy in Europe is NB-UVB and UVA1.…”
Section: Photobiology Of Ae Treatmentmentioning
confidence: 99%
“…Other devices such as 308-nm monochromatic excimer laser expand the therapeutic options in patients with localized and therapyresistant AE even though they can treat only limited surfaces. 182,183 Pulsed-dye laser for the treatment of chronic AE is still experimental. 184 Currently, the mainstay for phototherapy in Europe is NB-UVB and UVA1.…”
Section: Photobiology Of Ae Treatmentmentioning
confidence: 99%
“…Excimer‐Licht). Dieses konnte, neben der gezielten Behandlung von einzelnen Psoriasisplaques und etwas geringerer Wirkung bei der palmoplantaren pustulösen Psoriasis , auch bei der atopischen Dermatitis und der Vitiligo erfolgreich eingesetzt werden. Ebenso ist die Excimer‐Therapie bei der Alopecia areata des Erwachsenen und unter strenger Indikationsstellung bei Jugendlichen wirksam einsetzbar.…”
Section: Uv‐b‐phototherapieunclassified
“…In open prospective studies, several authors demonstrated a complete response or a significant improvement in most patients after 4–6 weeks of treatment with a cumulative dose >20 J/cm 2 UVA 16,20 . The targeted UVB excimer laser therapy is able to penetrate the parakeratotic hyperkeratosis because of the exact MEDI doses, which is 4–5 times that of the MED 8 …”
Section: Discussionmentioning
confidence: 99%